Evaluation of Burn Injuries and Epidemiological Factors in Patients Hospitalized in Shohada Mehrab Hospital in Yazd-Iran 2019 - moslem heydaripur; mohammad mehdi bahri; Ebrahim SHeykhi (Shahid Sadoughi University of Medical Sciences, 2021)
Introduction: Burn injuries are among the most important causes of disability and medical problems in the world. Weakness and inability of the burn is greater than the pain of the burn. Methods: This is a cross-sectional study-analysis in which the case of 126 patients admitted to the Shohada Mehrab Hospital, affiliated to the Shahid Sadoughi University of Medical Sciences in Yazd during the first six months of 2019, has been reviewed. Data were collected in a checklist designed by the researcher, and demographic variables and using the chi-square test, mean comparison, and using descriptive and analytical statistics and linear regression in the SPSS V.24 software was analyzed (p>0.05). Results: The findings of this study stated that  73.8% (93people) of patients were male and 26.2% (33 people) were female. 67.5% (85 people) were burned with thermal flames (p>0.019) and 13.5% (17 people) with boiling water (p>0.44). 77% (97 people) of home accidents, 22% (28 people) occurred at work, and 1% at other places (farm, car, etc.). 57% of these patients were 20% and 31% between 21-40 percent burns, burns, 22% between 41-60 percent burns and burns 11% between 61-80 percent and 5 percent are between 81-100 percent burned. This study results showed that the main cause of burns is fire (67.5%). Conclusion: The results of this study showed that most burns are among men, and about 70% of deaths are among men. The average length of hospital stay was 12 days, 22 patients died, and the fatality rate was 17.5%. This study showed that 67.5 % of burns were of the thermal type and hot water and hot liquids were the next cause of burns (13.5 %). Effective factors are fatality, patient age, and total body surface area (TBSA). 77% of burns occurred at home, 22% at work, and 1% at other places (farm, car, etc.). High incidence of burns and the loss of active community force will result in cost and disability. Treatment of burns requires a long hospital stay, which in addition to the high cost, can cause mental and psychological injuries to the patient.   Keywords: Burn, Epidemiology, Flame, Patient burn, Yazd